Environmental constraints to nodulation and nitrogen fixation of Phaseolus vulgaris L. in Tanzania. I. A survey of soil fertility, root nodulation and multi-locational responses to Rhizobium inoculation - Amijee, F; Giller, Kenneth E. (1998)
A survey of selected fields in bean growing regions of Tanzania and a more detailed survey of bean fields in the Lushoto area of northern Tanzania were carried out to establish soil properties limiting the extent of root nodulation of Phaseolus vulgaris L. Soil samples were collected and soil pH, organic matter content, cation exchange capacity and concentrations of extractable P, K, Ca and Mg determined. Plant vigour and nodulation were recorded and indigenous populations of rhizobia nodulating Phaseolus were estimated. The majority of soils were found to have very small concentrations of extractable P and this was associated with poor nodulation and poor plant vigour. In most cases there were reasonable populations of soil rhizobia present (102-104 cells/g soil) but plants were well nodulated only when soil P concentrations were adequate. A series of trials which included treatments where rhizobial inoculants were applied demonstrated no significant responses to inoculation unless the data were combined across the 10 sites. The data confirmed the need for experiments on-farm where soil nutrient concentrations (especially P) were generally much less than those found on research stations.